IFRS adoption in Turkey : roadmap, outcomes and practical implications - Gulec Atasoy, Bilgenur (2023)
The purpose of this study is to provide an in-depth analysis of the transition from Turkish Local GAAP to International Financial Reporting Standards (IFRS), with a focus on a real Turkish company. The study aims to illustrate the entire adoption process, including all necessary adjustments and changes required for compliance with IFRS. The research findings reveal that the adoption of IFRS poses significant challenges for Turkish companies. One of the primary challenges is the differing perspectives between Turkish Local GAAP and IFRS. While Turkish Local GAAP is based on tax principles, IFRS is principle-based, making it difficult for companies to adjust their accounting practices to the new standards. Moreover, the rules, calculations, and presentations under IFRS are often different from those under Turkish Local GAAP, requiring companies to make significant changes to their financial statements. This study offers a unique perspective on the implementation and application of IFRS, using real company cases to demonstrate how local statutory accounting is being prepared for IFRS, and how local GAAP is being harmonized with IFRS. The implications of this research are beneficial for businesses seeking clear guidance on the understanding of IFRS adoption. The research also contributes to the broader literature on IFRS adoption, offering valuable insights for researchers interested in the topic.